2018
DOI: 10.1080/02640414.2018.1464744
|View full text |Cite
|
Sign up to set email alerts
|

Reducing prolonged sedentary time using a treadmill desk acutely improves cardiometabolic risk markers in male and female adults

Abstract: This study evaluated the acute effects of interrupting prolonged sitting with an accumulated 2 h of light-intensity walking on postprandial cardiometabolic risk markers. In this randomised crossover trial, 24 participants (twelve males) aged 18-55 years took part in two, 6.5 h conditions: 1) prolonged sitting (SIT) and 2) sitting interrupted hourly with 20 min light-intensity treadmill desk walking at between 1.2-3.5 km/h (INT-SIT). Standardized meals were provided at 0 h and 3 h. Blood samples and blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 35 publications
1
64
0
Order By: Relevance
“…6,11). Conversely, 2 studies [46,72] reported no sex interactions for any outcomes when sitting was interrupted by light or moderate walking. Both sex specific PA break protocols or the underlying mechanisms, such as oestrogen levels [48][49][50][51], responsible for any possible sex divergent metabolic responses to PA breaks could be avenues for further research.…”
Section: Other Biasmentioning
confidence: 99%
“…6,11). Conversely, 2 studies [46,72] reported no sex interactions for any outcomes when sitting was interrupted by light or moderate walking. Both sex specific PA break protocols or the underlying mechanisms, such as oestrogen levels [48][49][50][51], responsible for any possible sex divergent metabolic responses to PA breaks could be avenues for further research.…”
Section: Other Biasmentioning
confidence: 99%
“…This is in agreement with studies in healthy able-bodied individuals. 15,35 However, reductions in triglyceride and blood pressure levels have been observed in other studies with healthy 36,37 and overweight/ obese adults. 17 One study in which triglycerides were attenuated over a single day used larger volumes of physical activity compared to the present study (ie, 20 minutes of light-intensity walking every hour).…”
Section: Discussionmentioning
confidence: 80%
“…17 One study in which triglycerides were attenuated over a single day used larger volumes of physical activity compared to the present study (ie, 20 minutes of light-intensity walking every hour). 37 It is thus possible that the lower energy expenditure and localized muscular contractions were insufficient to yield a change in the present study. Other studies that have demonstrated attenuation in postprandial triglycerides were in response to a test meal provided the day after breaking up sitting.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies have failed to observe a reduction in postprandial insulin [3,5,27] or change in the insulin-signalling pathway [6] in response to 2 min of light or moderate-intensity walking every 20 min over a single day, although these studies similarly were not powered to detect changes in these outcomes. Postprandial insulin reductions occurred in response to 2-5 min of light or moderate-intensity PA every 20-30 min and 20 min of light walking every hour in other studies that included larger sample sizes [10,14,20,30,32]. Future studies should thus be adequately powered to detect changes in postprandial glucose and insulin to provide a greater understanding of the mechanistic regulation in response to interrupting sedentary time.…”
Section: Discussionmentioning
confidence: 95%